Incidence of Soybean Mosaic Disease in East Java Province - Andayani, Wuye Ria; Sumardiyono, Y. B.; Hartono, Sedyo; Yudono, Prapto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
The objectives of this study were: 1) to identify the mosaic symptom severity and the incidence the virus and relate these to soybean yield reduction is four regions of East Java; 2) diagnostic of the symptom using Indirect ELISA, RT-PCR and electron microscope observation. Results from experiments indicated that soybean plants infected with SMV and CMMV, alone or in combination produced mosaic symptom. Incidence of the virus, as judged by symptomatology, ranged from mild to severe infection the percentage of plants being from 13.42-30.10%. Soybean plants with mosaic symptom caused SMV from an early stage of development (14-28 days after planting). Soybean mosaic virus belongs to the virus family Potyviridae. Specific DNA fragment of 1687 bp was successfully amplified from soybean infected by SMV isolate Ngawi, Madiun, Magetan, and Ponorogo. Specific DNA fragment of 1385 bp was successfully amplified from SMV by CI coding region. The mosaic symptom on soybean plant (28-42 days after planting) caused CMMV. Flexious virus particle 650 nm in length was observed on electron microscope. It caused local lesions on Chenopodium amaranticolor, but not detected by I ELISA with antiserum SMV and RT-PCR with universal primer. Keywords: SMV, CMMV, I.ELISA, RT-PCR.